DZIENNIKARSKIE ZDJĘCIA IGRZYSK OLIMPIJSKICH Z LAT 1988-2016 W KONKURSIE WORLD PRESS PHOTO - Piechota, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article aims to investigate themes in photographs taken by visual journalists from around the world. The analysed images have received awards in the Sports category of the World Press Photo Contest, and were taken during the Summer and Winter Olympic Games in the years 1988–2016. Research has demonstrated that at a time when the games are predominantly televised, photojournalism has to some extent become liberated from its informational role. In sports coverage, this form of journalism has thus begun searching for a symbolic dimension of the Olympiads. Basing on Roland Barthes’s theory that every photograph has a studium and a punctum, the author of the article studies eighteen images, which she arranges into matching pairs. The analysis shows that the award-winning photographs, taken during the Olympic Games from Seul to Rio de Janerio, successfully encapsulate a wide range of human emotions and behaviour, a quality which transforms these images into emblems of athletic effort.